Formulation of Anti-Aging Cream from Keratin Protein - Nurhamizah, Ahmad Zaini (2013)
Ageing is the phase where the body efficiency and metabolic activities decline after reaching maturity stage. The presence of free radical can cause alterations in collagen and make changes to membrane features. A large quantity of chicken feather is available as a waste product in Malaysia. Chicken feathers have high percentage of keratin protein content and can be a suitable protein source. Research was conducted using the keratin protein as the main component for the formulation of anti-aging cream. The difference between the formulations was on the concentration of keratin protein and the chemical that are used. The process involved are first dissolved the chemical in aqueous phase and heated up at 70°C. Then, the other component was mixed and heated up at 70°C. The oily phase was added to the aqueous phase and pre-emulsified. All the mixture was emulsified with homogenizer for the uniform mixing. The analysis by FTIR showed the presence of carboxyl, alcohol and amino groups. Clinical trial was done on rabbit for toxicology test. As conclusion, anti-aging cream can be produced from the keratin protein. The anti-aging cream was undergoing another analysis to check whether it is effectiveness.